Notarial Practice and Article 2(1) PDKP INI 2017 Compliance in Malang Raya - Novita Sri Desi; Sihabudin Sihabudin; Arini Jauharoh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
PDKP INI No. 1/2017 is a regulation formulated by the Indonesian Notary Association (INI) that governs the limit of the reasonable number of deeds a Notary may execute in a single day. Article 2, paragraph (1) of the regulation stipulates a maximum of 20 (twenty) deeds per day. However, in practice, several Notaries in the Malang Raya region still exceed this threshold. This research aims to analyze the contributing factors behind these violations and the resulting legal consequences. Employing a socio-legal research method with a sociological-juridical approach, the study identifies legal factors, law enforcement, societal influences (including Notaries who exploit the regulation), and cultural considerations as primary causes of non-compliance. The consequences of these violations include the degradation of the deed’s status into a private deed due to procedural irregularities, as well as professional sanctions imposed on the Notary. In response, it is recommended that the regulation concerning the maximum number of deeds executed daily by a Notary be revised to ensure clarity and effectiveness.